APPLICATION OF LARGE LANGUAGE MODELS IN ENTERPRISE AUTOMATION - Tsymbal, A.S. (SWorld-Ger Conference proceedings, 2025)
The paper explores the integration of large language models (LLMs) into enterprise automation workflows, focusing on their role in optimizing decision-making, document processing, and customer interaction systems. The study outlines key architectures and